Bioremediation of tannery effluent and its impact on seed germination (blackgram and sunflower) - Karthikeyan, B., Mythili, K*. and (Current Botany, 2011)
In this study, we attempted two investigational systems: one is treatment of tannery effluent by aerobic bacterial consortium and the other is impact of treated and untreated effluent on seed germination. For the effluent treatment, heavy metal resistant bacteria were isolated from tannery effluent. Among them, Bacillus, Pseudomonas and Micrococcus were selected for the further studies. The selected isolates were tested for their efficiency on the bioremediation of tannery effluent. The physico-chemical properties such as colour, odour, pH, electrical conductivity, total solids, suspended solids, dissolved solids, BOD, COD, chromium, zinc, iron, nickel were found decreased in effluent after 72 hrs. The study of seed germination (Blackgram and Sunflower) was carried out at 0, 20, 40, 60, 80, 100% concentrations of treated and untreated effluent using soil sowing method. Shoot length, fresh weight, dry weight and chlorophyll content showed an increase when treated effluent was tested whereas a decrease of growth was noticed in untreated effluent tested seedlings. The results revealed that effluent treated by aerobic microorganisms has no negative impact on the seed germination and can be effectively used for irrigation.